WHAT MAKES USERS INVEST IN GAMING APPLICATION OF SMARTPHONES? - chitranshbushal, Sujata Joshi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The mobile gaming industry started in 1994, and millions of games belonging to different genres have been developed since its inception. The mobile gaming applications cover a large customer base, and they have been among the highest revenue-generating categories of smartphone applications. A significant number of free smartphone games are available currently, but many users opt for the paid ones. The objective of this paper is to determine the factors which make the users addicted to mobile games and influence them to make purchases in it. Here, the factors have been broadly divided into three categories viz. social attributes (mass influence and peer influence), personal attributes (self-efficacy and personal motivation) and attributes of paid game applications (perceived price, perceived value. To achieve the above objectives; data was collected and evaluated from 135 respondents. Highlighted critical factors may provide guidance to mental health patients and professionals.